Long-Chain Omega-3 Fatty Acids Supplementation Accelerates Nerve Regeneration and Prevents Neuropathic Pain Behavior in Mice - Silva, Rafaela V.; Oliveira, Julia T.; Santos, Bruna L. R.; Dias, Fabiana C.; Martinez, Ana M. B.; Lima, Cleverton K. F.; Miranda, Ana L. P. (Frontiers in Pharmacology, 2017)
Fish oil (FO) is the main source of long chain omega-3 polyunsaturated fatty acids (ω-3 PUFAs), which display relevant analgesic and anti-inflammatory properties. Peripheral nerve injury is driven by degeneration, neuroinflammation, and neuronal plasticity which results in neuropathic pain (NP) symptoms such as allodynia and hyperalgesia. We tested the preventive effect of an EPA/DHA-concentrate fish oil (CFO) on NP development and regenerative features. Swiss mice received daily oral treatment with CFO 4.6 or 2.3 g/kg for 10 days after NP was induced by partial sciatic nerve ligation. Mechanical allodynia and thermal hypernociception were assessed 5 days after injury. CFO 2.3 g/kg significantly prevented mechanical and thermal sensitization, reduced TNF levels in the spinal cord, sciatic MPO activity, and ATF-3 expression on DRG cells. CFO improved Sciatic Functional Index (SFI) as well as electrophysiological recordings, corroborating the increased GAP43 expression and total number of myelinated fibers observed in sciatic nerve. No locomotor activity impairment was observed in CFO treated groups. These results point to the regenerative and possibly protective properties of a combined EPA and DHA oral administration after peripheral nerve injury, as well as its anti-neuroinflammatory activity, evidencing ω-3 PUFAs promising therapeutic outcomes for NP treatment.